Muhammad ‘Abduh’s reformism: the modes of its dissemination in pre-independent Malaysia - Zakariya, Hafiz (Global Academic Excellence (GAE), 2020)
Muhammad ‘Abduh (1849-1905) was a prominent scholar, pedagogue, mufti ‘alim, theologian and reformer. Though trained in traditional Islamic knowledge, ‘Abduh, who was influenced by the ideas of Jamal al-Din al-Afghani, became discontent with the existing methods of traditional Islamic learning. Based in Egypt, ‘Abduh led the late 19th-century Muslim reform to revitalize some aspects of Islamic doctrine and practice to make them compatible with the modern world. This reformist trend called for the reform of intellectual stagnation, revitalization of the socio-economic and political conditions of the ummah, and to make Islam compatible with modernity. ‘Abduh’s progressive reformism found following in various parts of the Muslim world including the Malay Archipelago. Among those influenced by ‘Abduh in the region were Sheikh Tahir Jalaluddin and Abdullah Ahmad in West Sumatra, Syed Sheikh al-Hadi in Malaya, and Kiyai Ahmad Dahlan in Yogyakarta. Though there is increasing literature on Muslim reformism, few worksexamine the social history of the transmission of ideas from one part of the Muslim world to another. Thus, this study analyzes how ‘Abduh’s reformism was transmitted to pre-independent Malaysia.